Four Views of Science and Religion - Mamedov, Eminaga; Məlikov, Ələddin (Scholarya Demo Journal of Ruby, 2021)
The relationship between science and religion has been marked by controversial debates throughout history. This tension was sometimes weak and sometimes more severe. When studying the relationship between science and religion, it is essential to analyze the situation in each field of science separately before examining the relationship as a whole. Similarly, this issue needs to be addressed in religions. As a result, each religion has its own characteristics. The study of the relationship between science and religion has a special and deep layer, thus research in this area should always be carried out seriously. Does science contradict religion? Do science and religion belong to different fields? Are science and religion always in discussion and interaction? Are science and religion generally complementary and always integrated? The answers to all these questions are given in full in this article. This article is a translation of first chapter of Ian Barbour's book When Science Meets Religion, in which above mentioned questions are considered. Ian Barbour divides these relationships into four main categories with examples and explains each one separately. These relationships generally reveal the origin, process, and outcome of the problem. Thus, it characterizes and embodies existing theories, and as we hope it opens the way to a new scientific research, and deeply contributes to the formation of new ideas.